WISATA GOA PINDUL SEBAGAI DAYA TARIK MINAT WISATAWAN: STUDI TENTANG KARAKTERISTIK, DAN MOTIVASI - Berliana, Naumi; Saptoto, Robertus; Merita, Thasia (Pengelola Jurnal Politeknik Negeri Ketapang, 2025)
Goa Pindul, located in Gunungkidul Regency, Yogyakarta, has emerged as a notable geotourism destination that integrates adventure-based and educational experiences within a karst landscape. This study aims to examine the demographic characteristics and motivational drivers of visitors, while also identifying behavior-based segmentation patterns. Employing a descriptive qualitative approach, data were collected through in-depth interviews by 10 informans, participant observation, and supplementary documentation. The findings reveal four dominant motivational dimensions: the desire to escape routine, the pursuit of knowledge and novel experiences, the attraction to adventure and thrill, and the intention to strengthen social bonds. Each segment exhibits distinct behavioral orientations and varying levels of environmental awareness. The study highlights the importance of adaptive, segment-specific management strategies to optimize visitor experiences and support sustainable destination development. These insights are expected to contribute to more targeted policy interventions and strategic planning for geotourism in karst regions.